Aligning professional development, school self-evaluation and principals' performance standards: a UAE case study. (15th March 2019) - Blaik Hourani, Rida; Litz, David R.
ABSTRACT: The Abu Dhabi Education Council (ADEC) has introduced professional development (PD) plans and professional standards for school administrators. This was initiated to galvanise the ongoing school reforms. In addition, the Irtiqaa Framework, a school self-evaluation programme that contributes to the broad agenda of school reforms and changes, is currently implemented in public schools throughout the entire Emirate of Abu Dhabi. This study explores school administrators' experiences of the PD offered in their schools, querying how aligned they are with the school self-evaluation and principal's performance standards. The research employed a qualitative case-study approach. Semi-structured interviews were used as tools for data collection and they were conceptualised within the framework of the administrators' performance standards and school-self-evaluation-Irtiqaa documents provided by ADEC. Researchers conducted semi-structured interviews with 14 school administrators, including principals, vice principals, and academic principals that represent six cycle-1 public schools. Findings and recommendations presented highlight the areas of improvement needed for more effective professional development that is not only in synchrony with school demands in times of change, but also in alignment with professional requirements that enhance effective school self-evaluation.